Influência de treinos e jogos sobre a força de isquiossurais e fadiga neuromuscular em atletas de futebol - Thales Duarte Lopasso (2023)
Muscle hamstring injuries represent a significant concern for the health of soccer athletes. It is believed that the occurrence of these injuries results from the combination of multiple risk factors associated with exposure to the sport. It's natural that engagement in soccer can lead to changes in physical capacities (including modifiable risk factors), such as increased fatigue, reduced hamstring strength, and heightened asymmetry in this muscle group. Despite the limited amount of literature investigating modifiable risk factors over the season, there are few studies that seek to understand which training and game variables are most closely related to these modifiable risk factors. Therefore, the aim of this current study is to determine the impact of training and matches on the isometric strength of the hamstring muscles and neuromuscular fatigue during a period of the competitive season in young soccer athletes. This is a retrospective study, encompassing evaluations and records from the club covering the period from July to November 2022. The study involves a convenience sample comprising players from the U-20 category (aged between 18 and 20 years) of a professional soccer team. All players in this category who had an active contract with the club and were not under any injury condition (preventing readiness for a full soccer match) at the beginning of data collection wereinvited to participate. However, those with a history of hamstring muscle injury within the corresponding six months (from July 2022 onwards) were excluded. Weekly, the athletes began with a standardized warm-up, proceeded to the Countermovement Jump (CMJ) assessment, andsubsequently, evaluation of hamstring muscle strength on the NordBord platform. After the assessment procedures, the athletes followed the training routine planned by the football club. Throughout the mentioned period, the athletes continued regular use of GPS tracking, with weekly evaluations and/or assessments conducted 48 hours after an official match. In total, 22 athletes were evaluated. To assess the association between monitoring variables and load variables over the follow-up period, mixed-effects generalized linear models were employed. High-intensity running at various levels was associated with isometric hamstring muscle strength tests and vertical countermovement jump. Increases in distances covered above 20 km/h, between 20 and 24.9 km/h, between 25 and 29.9 km/h, as well as the number of sprints performed above 25 km/h, were associated with decreased hamstring strength asymmetry.Moreover, the number of sprints performed above 25 km/h was linked to increased vertical countermovement jump height. The primary factor contributing to reduced asymmetry was linked to increased isometric strength in the left lower limb.